Novel Chitinase Gene LOC_Os11g47510 from Indica Rice Tetep Provides Enhanced Resistance against Sheath Blight Pathogen Rhizoctonia solani in Rice - Richa, Kamboj; Tiwari, Ila M.; Devanna, B. N.; Botella, Jose R.; Sharma, Vinay; Sharma, Tilak R. (Frontiers in Plant Science, 2017)
Sheath blight disease (ShB), caused by the fungus Rhizoctonia solani Kühn, is one of the most destructive diseases of rice (Oryza sativa L.), causing substantial yield loss in rice. In the present study, a novel rice chitinase gene, LOC_Os11g47510 was cloned from QTL region of R. solani tolerant rice line Tetep and used for functional validation by genetic transformation of ShB susceptible japonica rice line Taipei 309 (TP309). The transformants were characterized using molecular and functional approaches. Molecular analysis by PCR using set of primers specific to CaMv 35S promoter, chitinase and HptII gene confirmed the presence of transgene in transgenic plants which was further validated by Southern hybridization. Further, qRT-PCR analysis of transgenic plants showed good correlation between transgene expression and the level of sheath blight resistance among transformants. Functional complementation assays confirmed the effectiveness of the chitinase mediated resistance in all the transgenic TP309 plants with varying levels of enhanced resistance against R. solani. Therefore, the novel chitinase gene cloned and characterized in the present study from the QTL region of rice will be of significant use in molecular plant breeding programme for developing sheath blight resistance in rice.